Evaluation and management of ileal pouch-anal anastamosis (IPAA) complications in pregnancy, and the impacts of an IPAA on fertility. Issue 5 (25th May 2023) - Prentice, Ralley E.; Wright, Emily K.; Flanagan, Emma; Kamm, Michael A; Goldberg, Rimma; Ross, Alyson L.; Burns, Megan; Bell, Sally J.
Abstract : Restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA) remains the preferred surgical option for medically refractory ulcerative colitis. Management of individuals with an IPAA prior to and during pregnancy presents challenges that can have serious consequences. Infertility, mechanical obstructive and inflammatory pouch complications are frequently encountered in pregnant women with an IPAA. Mechanical obstructions occur due to a variety of underlying aetiologies, including stricturing disease, adhesions and pouch twists. Conservative management of such obstructions often results in resolution of symptoms without a need for endoscopic or surgical intervention, although endoscopic decompression may be attempted in isolation or as a bridge to definitive surgical intervention. Parenteral nutrition, and early delivery, may also be necessary. Faecal calprotectin and intestinal ultrasound, both of which are accurate in pregnancy, are useful in the setting of suspected inflammatory pouch complications, in some circumstances allowing for avoidance of pouchoscopy. Penicillin-based antimicrobials can be considered first line in pregnancy for the management of pouchitis and pre-pouch ileitis, and biologics can be safely instituted in the setting of refractory disease or suspected Crohn's disease-like inflammation of the pouch or pre-pouch ileum. Pragmatism, clear patient communication and multidisciplinary discussion are essential in approaching pregnant women with complications of an IPAA, particularly given the lack of definitive evidence to guide therapeutic decisions.